ANALISIS RESPONS AFEKTIF SISWA TERHADAP PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF INDONESIA VIRTUAL TOUR (Pada Materi Kondisi Geografis Indonesia Kelas V SD) - Septiani Fauziyah, Vina; Isrok'atun; Rukmana, Kusman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine 1) Students' affective responses to the use of Indonesia Virtual tour learning media on the material of Indonesia's geographical conditions, 2) Factors that influence students' affective responses to the use of Indonesia Virtual tour learning media on the material of Indonesia's geographical conditions. This study uses a descriptive qualitative approach with a case study research type. With the research subjects being fifth grade students of Gunungsari State Elementary School, located on Jl. Sindang Taman, RT 02/03, Jatimulya, North Sumedang District, Sumedang Regency, West Java Province. Research data collection techniques were obtained through observation, interviews and questionnaires. The conclusions from the results of this study are first, students' affective responses to the use of Indonesia Virtual tour interactive learning media in learning the material of Indonesia's geographical conditions generally show good results. This is shown through students' attention, activeness, involvement, and enthusiasm during the learning process. Students are able to participate in learning activities, such as discussions, questions and answers, and media exploration, and show positive attitudes such as respecting friends' opinions and working together in groups. Second, students' affective responses are influenced by internal and external factors. Internal factors include student interest, motivation, and self-confidence, while external factors include the use of interactive learning media, the teacher's role, and the classroom atmosphere. The use of the Indonesia Virtual tour media increased student interest because it presented material on Indonesia's geographical conditions visually and concretely, making it easier for students to understand.